Rebuilding Trust: Ireland’s CSR Plan in the Light of Caritas in Veritate - Kearns, Alan J. (Journal of business ethics, 2017)
This paper seeks to contribute to the discussion on national corporate social responsibility (CSR) plans from the perspectives of the three logics as articulated in Caritas in Veritate, by using the Irish national CSR plan as an example. Good for Business, Good for the Community: Ireland’s National Plan on Corporate Social Responsibility 2014–2016 maintains that CSR activities can enable organisations to build relationships and trust with communities. One of the consequences of the 2008 financial crisis was the decrease in trust in banking systems and in business more broadly. It is well recognised that relationships of trust are essential to the life of the market, the state and civil society. Pope Emeritus Benedict XVI’s Caritas in Veritate contends that corresponding to the life of the market, the state and civil society are three logics: the logic of exchange (i.e. giving to acquire), the logic of public obligation (i.e. giving through duty) and the logic of gift (i.e. giving due to solidarity). This paper proposes that the normative framework of the three logics of Caritas in Veritate can be read into the Irish national CSR plan. This paper argues that the examples of CSR initiatives proffered by the plan could point organisations in the direction of the logic of gift and therefore enable the rebuilding of relationships of trust with citizens and communities.